The types of idiom and their meaning in michael jackson “thriller” album - Sukrawan, I Kadek Adi; Utami, Ni Made Verayanti (Journal of Language and Applied Linguistics, 2020)
This study is entitled “The Types of Idiom and Their Meaning in Michael Jackson “Thriller” Album”. This study is needed because it was found that a lots of non natives English speakers was often didn’t understand about idiom and their uses, oftentimes this leads to the miss communication. The purpose of this study is to give the non native English speaker about idiom knowledgably and their meanings in their practical uses. The method used in this study was qualitative-descriptive method combine with library research method in collecting the data. The result in this study showed that there were found 9 types of idiom in this album, they were 4 types of partial idiom (44, 44%) and 5 types of total idiom (55, 56). For the types of meaning there were found 9 types of meaning, they were 4 connotative meaning (44, 44%) and 5 affected meaning (55, 56%).